2023
DOI: 10.1093/hr/uhad067
|View full text |Cite
|
Sign up to set email alerts
|

ALA reverses ABA-induced stomatal closure by modulating PP2AC and SnRK2.6 activity in apple leaves

Abstract: 5-Aminolevulinic acid (ALA), known as a new natural plant growth regulator, can reverse abscisic acid (ABA)-induced stomatal closure. The protein phosphatase 2A (PP2A) played an important role in regulation of stomatal movement by ALA and ABA; however, the underlying molecular mechanisms remain unclear. Here, we report that ALA promotes MdPP2A activity and gene expression in the leaf epidermis of apple (Malus × domestica Borkh.), and expression of the catalytic subunit MdPP2AC was most significantly correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 81 publications
(122 reference statements)
2
9
0
Order By: Relevance
“…In tobacco, ABA treatment could inhibit expression of NtMYB184 (a flavonol-specific activator), which reduced production of flavonols and thus increased ROS levels to regulate stomatal closure [ 65 ]. ALA, known as a new natural plant growth regulator, can reverse ABA-induced stomatal closure [ 140 ]. In apple, ALA treatment enhanced protein abundance and phosphorylation of protein phosphatase 2AC (MdPP2AC), which promoted the interactions of different PP2A subunits and increased holoenzyme activity [ 140 ].…”
Section: Cascade Transcriptional Regulation Of Flavonol Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“…In tobacco, ABA treatment could inhibit expression of NtMYB184 (a flavonol-specific activator), which reduced production of flavonols and thus increased ROS levels to regulate stomatal closure [ 65 ]. ALA, known as a new natural plant growth regulator, can reverse ABA-induced stomatal closure [ 140 ]. In apple, ALA treatment enhanced protein abundance and phosphorylation of protein phosphatase 2AC (MdPP2AC), which promoted the interactions of different PP2A subunits and increased holoenzyme activity [ 140 ].…”
Section: Cascade Transcriptional Regulation Of Flavonol Biosynthesismentioning
confidence: 99%
“…ALA, known as a new natural plant growth regulator, can reverse ABA-induced stomatal closure [ 140 ]. In apple, ALA treatment enhanced protein abundance and phosphorylation of protein phosphatase 2AC (MdPP2AC), which promoted the interactions of different PP2A subunits and increased holoenzyme activity [ 140 ]. Phosphorylated PP2A interacted with and dephosphorylated MdSnRK2.6 (sucrose non-fermenting 1-related protein kinase 2.6), which induced flavonol accumulation and thus reduced ROS levels in the guard cells to open stomata [ 140 ].…”
Section: Cascade Transcriptional Regulation Of Flavonol Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of AtPP2AC-5 promoted the PP2A activity and conferred better growth of root and shoot of Arabidopsis under salt condition ( Hu et al., 2017 ). Our previous pharmacological and genetic studies with detached apple leaves showed that MdPP2AC was involved in ALA-ABA modulating stomatal movement ( Chen et al., 2023 ). In the regulation, MdPP2AC is positive for ALA signaling but negative for ABA signaling.…”
Section: Introductionmentioning
confidence: 99%
“…SnRK2.6 phosphorylation and dephosphorylation controls stomatal closing and opening ( Mustilli et al., 2002 ; Yoshida et al., 2002 ). In the previous study, we demonstrated that SnRK2.6 functioned at the downstream of PP2A signaling, involved in ALA-ABA regulation of apple stomatal movement ( Chen et al., 2023 ). Based on these studies, we hypothesized that ALA positively regulated PTPA and PP2AC expression to enhance PP2A activity, and then negatively regulated SnRK2.6 activity, which finally promoted stomatal opening and improved leaf photosynthetic efficiency of plants.…”
Section: Introductionmentioning
confidence: 99%